2016
DOI: 10.1121/1.4948754
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies, bandwidths and magnitudes of vocal tract and surrounding tissue resonances, measured through the lips during phonation

Abstract: The frequencies, magnitudes, and bandwidths of vocal tract resonances are all important in understanding and synthesizing speech. High precision acoustic impedance spectra of the vocal tracts of 10 subjects were measured from 10 Hz to 4.2 kHz by injecting a broadband acoustic signal through the lips. Between 300 Hz and 4 kHz the acoustic resonances R (impedance minima measured through the lips) and anti-resonances R¯ (impedance maxima) associated with the first three voice formants, have bandwidths of ∼50 to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In both cases, subjects were instructed to keep their tongue low in the mouth and produce a neutral vowel as in the Australian English pronunciation of "heard." The acoustic response of this shape approximates that of a cylindrical pipe, closed at the glottis end and open at the mouth end (Hanna et al, 2016b). FIG.…”
Section: Resonance-free Pitch Glide With Resistive Loadmentioning
confidence: 78%
See 2 more Smart Citations
“…In both cases, subjects were instructed to keep their tongue low in the mouth and produce a neutral vowel as in the Australian English pronunciation of "heard." The acoustic response of this shape approximates that of a cylindrical pipe, closed at the glottis end and open at the mouth end (Hanna et al, 2016b). FIG.…”
Section: Resonance-free Pitch Glide With Resistive Loadmentioning
confidence: 78%
“…Inspection of the pitch glides performed by the panel of subjects on the vowels in "who 'd," "hard, showed no significant correlation between the frequencies where pitch instabilities occurred and the measured values of f Sg1 or F1. Even if the measured bandwidths of R1 or Sg1 (both around 75 Hz in women-see Hanna, 2014;Hanna et al, 2016b) are considered, no significant correlation is apparent. One explanation for this was the likely use of at least some degree of resonance tuning, i.e., subjects can smoothly increase f R1 to keep f R1 above or around f o .…”
Section: E Constrained Pitch Glides With Mouth Ringmentioning
confidence: 98%
See 1 more Smart Citation
“…Hanna and al. proposed instead to increase this correction by a factor 5 [28]: we found that this change makes the transition to be close to u = 0. The estimation of acoustic radiation with aperture radius is an approximation, in particular it does not take into account inner reflexions [32].…”
Section: Plos Onementioning
confidence: 86%
“…air density and the speed of sound. To account for other surface losses in the waveguide, k was substituted with k = ω/c − jα, a ¼ 1:2e À 5 ffi ffi ffi ffi o p =0:01 as in Ref [28]. The waveguide length was similar to the length of the vocal tract (in average 16.5 cm).…”
Section: Plos Onementioning
confidence: 99%